Pengalaman Toleransi Beragama Belia Pelbagai Etnik - Khadijah Muda; Khairul Anwar Mastor; Fazilah Idris (Penerbit UTM Press, 2024)
This article presents youth experience towards religious tolerance in Malaysia. The sample consists of 500 respondents aged between 15 and 24 years old. The selection is done by a stratified random sampling of three main races selected from five different states. The questionnaire of socio-religious tolerance by Ahmad Tarmizi (2010) is used as research instrument. The data are analysed descriptively using SPSS 22.0. The findings show that the experience of respondents' religious tolerance is at a medium level, which is they often well-served by different religious people and sometimes receiving invitations for weddings, open houses andbeing told if there is death by different religious contacts. This indicates that the respondents' experience of religious tolerance is at a good level and most of them live in a tolerant society.